RETRACTED: The biopharmaceutical classiﬁcation of medicinal substances - G. V. Ramenskaya; I. E. Shokhin; Yu. I. Kulinich (Сеченовский вестник)
RETRACTED ARTICLEThe goal of this investigation is to describe the main types of medicines (b(biopharmaceutical classiﬁcation system (BCS) and biopharmaceutic classiﬁcation of drugs according to their solubility and metabolism (BDDCS). The methods of evaluation of biopharmaceutical properties (solubility and permeability) of medical substances are under consideration. The applicability of these systems in the evaluation interchange is viewed in relation to generic substances in vitro (procedure «bioveyver»).